Method for determining optimum frequency of stimules during electrical stimulation of skeletal muscles - Yeroshenko, O.; Prasol, I. (My University, 2022)
Electrical stimulation consists in such an effect of a pulsed electric current with a certain set of parameters on the patient's body, in which the necessary positive therapeutic effects occur. Electrical stimulation of skeletal muscles is especially common. It is an effective method of rehabilitation for various injuries and disorders, as well as an auxiliary method in the preparation of athletes. Existing devices, as a rule, have a number of standard modes; the possibilities for fine tuning of stimulus parameters are limited. This does not allow to adequately take into account the individual characteristics of the patient. At the same time, a lot depends on the chosen muscle, its properties, age, sex of the patient, etc. Therefore, it is quite important to determine a priori some parameters of current stimuli, in particular, its frequency.
Keywords: muscle; Electrical stimulation